Key Plant, Key Pest: Oleander (Nerium oleander) - Juanita Popenoe; Caroline Roper Warwick; Jacqueline Bourdon; Jianjun Chen (EDIS, 2019)
This series of Key Plant, Key Pests publications are designed for Florida gardeners, horticulturalists, and landscape professionals to help identify common pests associated with common Florida flora. This new 5-page publication, the tenth in the series, helps identify the most common pests found on oleander. This publication provides information and general management recommendations for oleander aphids, oleander caterpillars, sphaerosis gall, oleander leaf scorch, and scale. Written by Juanita Popenoe, Jacqueline Bourdon, Caroline R. Warwick, and Jianjun Chen, and published by the UF/IFAS Environmental Horticulture Department. https://edis.ifas.ufl.edu/ep574